Unsheltered [compact disc, unabridged] : a novel - Kingsolver, Barbara (Harper Audio, 2018)
The story of two families, in two centuries, who live at the corner of Sixth and Plum, as they navigate the challenges of surviving a world in the throes of major cultural shifts. In this mesmerizing story told in alternating chapters, Willa and Thatcher come to realize that though the future is uncertain, even unnerving, shelter can be found in the bonds of kindred, whether family or friends, and in the strength of the human spirit.